Effect of different fixative solutions on eyes with experimental proliferative vitreoretinopathy. Issue 2 (9th February 2015) - Nassar, Khaled; Lüke, Julia; Lüke, Matthias; Kamal, Mahmoud; Soliman, Mahmoud M.; Grisanti, Salvatore; Grisanti, Swaantje
Summary The aim of this study was to evaluate the use of different fixatives on the reliability of histopathological changes in a rabbit model of proliferative vitreoretinopathy (PVR). Twenty eyes from 10 rabbits were divided into four groups. The right eyes were used in two experimental groups (each n = 5), and the left, in two control groups (each n = 5). Using a newly developed scleral incision marker, an oblique scleral incision was standardized in the experimental groups, followed by intravitreal injection of 0.4 ml autologous blood and the left for wound repair for four weeks. Eyes were enucleated at four weeks. The groups differed in the type of used fixative solution (formaldehyde 4% vs. 1% buffered formaldehyde and 1.25% glutaraldehyde). The eyes were evaluated for the development of fibrosis, retinal detachment (RD), and processed for histopathology. Fibrous ingrowth of a variable degree was present in the experimental groups originating from the trauma site. Experimental eyes fixed with formaldehyde 4% had RD extension that was greater than that fixed in formaldehyde/glutaraldehyde mixture; however, the difference did not reach statistical significance (P = 0.15). This difference was not fully explained by the fibrosis which developed. In addition, in control groups, formaldehyde 4% induced a fixative‐dependent retinal separation that was absent in eyes fixed with formaldehyde/glutaraldehyde mixture (P = 0.03). In conclusion, a mixture of buffered formaldehyde 1% and glutaraldehyde 1.25% combined with standardized scleral incision resulted in consistent pathological changes. A reliable PVR model is a condition sine qua non to evaluate antifibrotic treatment strategies.